The mixed methods research workbook activities for designing, implementing, and publishing projects - Fetters, Michael D. (SAGE, 2020)
"Struggling to plan, complete, and write up a mixed methods project? Don't know where to begin or how to stay organized during the process? The Mixed Methods Research Workbook will provide you with the tools to break down a mixed methods research study into manageable pieces, providing practical information along with activities and exercises that are quickly and easily applicable to your own research. Starting with the language of mixed methods and identifying your research question, the book provides step-by-step workboxes that build on one another to help you build your research foundations, design your study, analyze your data, and plan your journal article or dissertation from beginning to end. Each chapter follows a familiar framework, starting with learning objectives for each piece of the mixed methods process. Readers have ample space in this text to write notes, fill out activities, and begin their process of actively designing and writing up a mixed methods study. This easy-to follow process gives readers an immediate structure to their projects. Exemplar boxes provide a starting framework, with the text encouraging deeper reflection on mixed methods challenges and opportunities. Stories from the field illuminate struggles and suggestions with the benefit of hindsight. Checklists at the end of each chapter help readers stay organized and key resources provide up-to-date lists of material for further study"--